2016
DOI: 10.1590/1519-6984.04815
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinvertebrate community in the Sinos river drainage basin, Rio Grande do Sul, Brazil

Abstract: Aquatic macroinvertebrate fauna is a relevant component of limnic continental aquatic ecosystems, playing an important role in several processes with relevant biocomplexity. The present study characterized the benthic macroinvertebrate fauna found in three hydric bodies in the Sinos river drainage basin regarding community structure. Sample was collected from January to December 2013 in three locations in the basin: the city of Caraá (29 °45'45.5"S/50°19'37.3"W), the city of Rolante (29°38'34.4"S/50°32'33.2"W)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In the current study, the macro-invertebrate communities' composition was higher when compared to other similar findings; From the identified classes of macroinvertebrates, an order of Insecta, the Hemiptera families have contributed the largest percentage (35.80%). Similarly, research conducted by Barros et al (2016) in the River Sinos basin revealed the dominance of the community of invertebrates represented by the taxa belonging to the class of Insecta. The dominance of Hemiptera families might be associated with the morphological and physiological adaptations such as the resistance of the eggs, the varied diet under the different life stages, and the presence of wings which make to disperse that enable them to access food and escape from predators (Ruppert and Barnes, 1996).…”
Section: Macroinvertebrate Diversity Abundance and Macrophyte Covermentioning
confidence: 84%
“…In the current study, the macro-invertebrate communities' composition was higher when compared to other similar findings; From the identified classes of macroinvertebrates, an order of Insecta, the Hemiptera families have contributed the largest percentage (35.80%). Similarly, research conducted by Barros et al (2016) in the River Sinos basin revealed the dominance of the community of invertebrates represented by the taxa belonging to the class of Insecta. The dominance of Hemiptera families might be associated with the morphological and physiological adaptations such as the resistance of the eggs, the varied diet under the different life stages, and the presence of wings which make to disperse that enable them to access food and escape from predators (Ruppert and Barnes, 1996).…”
Section: Macroinvertebrate Diversity Abundance and Macrophyte Covermentioning
confidence: 84%
“…Specific locations, such as the QBEZ, lie near human habitation zones, where the release of domestic sewage compounds pollutes river segments [56,57]. However, the elevated abundance of avian species within agricultural and pastoral regions may stem from the heightened nutrient concentration in these waters, fostering algal and zooplankton proliferation and subsequently amplifying bird populations [58][59][60][61][62][63]. Smakhtin similarly identified an augmented prevalence of avian species within the macroinvertebrate fauna of urban rivers, typically correlated with water pollution and anthropogenic disruptions [64].…”
Section: Discussionmentioning
confidence: 99%
“…Richness was negatively influenced by water turbidity and total dissolved solids, and the composition was influenced by water temperature, oxidation-reduction potential, turbidity, sediment organic matter, and orthophosphate. Many studies detected relationships between water physicochemical variables and macroinvertebrate communities in wetlands (Zimmer et al, 2000;Batzer et al, 2004;Stenert & Maltchik, 2007;Stenert et al, 2008;Tokeshi & Arakaki, 2012;Bischof et al, 2013;Strachan et al, 2015;Barros et al, 2016;Gleason & Rooney, 2017;Romero et al, 2017;Baldwin et al, 2018). Some authors detected reductions in macroinvertebraterichness with increasing turbidity (Batzer, 2013;Johnson et al, 2013;Sundberg et al, 2016;Baldwin et al, 2018).…”
Section: Discussionmentioning
confidence: 99%